Estimation of entropy in Amparo de São Francisco, Sergipe – Brazil (Research, Society and Development, 2021)
The entropy proposition was used to assess the fluctuations in rainfall, trying to understand or add more rainfall information about the region. Evaluate the fluctuations of daily, monthly and annual rainfall data for Amparo de São Francisco and discuss their water availability, observing the entropy methodology for dry and rainy blocks and their standard deviations, between 1964-2020. The annual daily rainfall series were provided through the rainfall probability distribution function and the annual average of entropy, being calculated for each year through the information of this average. The “bit” unit was used to calculate the element under study, meaning binary digit and the smallest numerical unit accepted were the values ​​of 0 or 1. The yield of information results in a reduction in entropy, and vice-versa. Entropy becomes zero when there is absolute certainty that a certain event will occur, or statistically, when all but one probability in the set is zero.